2017
DOI: 10.1051/epjconf/201715305009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Radiation Fields for Assessing Concrete Degradation in Biological Shields of NPPs

Abstract: Abstract. Life extensions of nuclear power plants (NPPs) to 60 years of operation and the possibility of subsequent license renewal to 80 years have renewed interest in long-term material degradation in NPPs. Large irreplaceable sections of most nuclear generating stations are constructed from concrete, including safety-related structures such as biological shields and containment buildings; therefore, concrete degradation is being considered with particular focus on radiation-induced effects. Based on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Remec et al (2016b) showed that, for the neutron spectra in the biological shield of two-loop and three-loop (the number of reactor cooling circuits) PWRs, neutrons with energies above 0.1 MeV contribute more than 95% of all atom displacements in several widespread aggregate minerals, while neutrons with energies above 1 MeV cause only about 20 to 25% of the total atom displacements, as shown in Fig. 1 (Remec et al 2016a). The conclusions were similar when, instead of atom displacements, neutron-induced absorbed dose in minerals was considered.…”
Section: Energy Spectra and Damage Energiesmentioning
confidence: 96%
“…Remec et al (2016b) showed that, for the neutron spectra in the biological shield of two-loop and three-loop (the number of reactor cooling circuits) PWRs, neutrons with energies above 0.1 MeV contribute more than 95% of all atom displacements in several widespread aggregate minerals, while neutrons with energies above 1 MeV cause only about 20 to 25% of the total atom displacements, as shown in Fig. 1 (Remec et al 2016a). The conclusions were similar when, instead of atom displacements, neutron-induced absorbed dose in minerals was considered.…”
Section: Energy Spectra and Damage Energiesmentioning
confidence: 96%
“…These rather deep damage penetration are the result of the very high total flu-ence exposure assumed: 10 +12 n.cm −2 s −1 which leads to a total fluence of about 1.6 × 10 +21 n.cm −2 after 50 years of operation. Such a flux is one to two orders of magnitude higher than the estimated bounding value for PWR CBSs (Esselman and Bruck, 2013;Remec et al, 2014 Finally, Andreev and Kapliy (2014) were the first to develop an 1Dcylindrical model accounting for the radiation-induced deformation and, the loss of elastic modulus induced by temperature and irradiation. However, the fluence (up to 5 × 10 +24 n.cm −2 , the temperature (500 • C) and the ge-…”
Section: Structural Models Of Irradiated Concretementioning
confidence: 98%
“…Hence, BWRs CBS are likely to be relatively immune to irradiation effects since the effets of radiation on concrete mechanical and physical properties are observed for fluence above 1.0 × 10 +19 n.cm −2 . The flux attenuation (Remec et al, 2014) in ordinary concrete is about one order of magnitude per ≈ 12 to 15 cm (5 to 6 in.). Hence, radiation-induced effects are expected to be predominant primarily in the same region depending on the actual fluence at the CBS inner diameter although constrained radiation-induced volumetric expansion (RIVE) could potentially develop detrimental stresses deeper in the CBS wall.…”
Section: Structures Of Interestmentioning
confidence: 99%
See 2 more Smart Citations